The influence of vegetation pattern on the productivity, diversity and stability of vegetation: The case of 'brousse tigree' in the Sahel - Hiernaux, Pierre H.Y.; Gerard, Bruno G. (Elsevier, 1999)
Sample sites of 'brousse tigree' and related vegetation types are described for Mali and Niger. Species composition and physical structure of the herbaceous layer as well as woody plant population were recorded at all sites together with data on soils and natural resource management. Herbage yield was measured whereas foliage yield and wood mass were calculated using allometry equation calibrated for each species. 'Brousse tigree' is characterized by the regularly alternating bare-soil stripes with dense linear thickets arranged perpendicularly to the slope. There was no clear superiority in total plant production of 'brousse tigree' when compared to neighbouring site with diffuse vegetation. However, the pattern of 'brousse tigree' tended to favour woody plant yield to the detriment of herbage yield. The number of herbaceous species recorded per site (22-26) was slightly above Sahelian vegetation average despite low number of species per I-ml quadrat (6-9). bare soil excluded. This species richness reflects the diversity in edaphic niches resulting from the redistribution and local concentration of water resources and shade. The high spatial heterogeneity and species richness of the herbaceous layer in 'brousse tigree' did not attenuate the interannual variation in herbage yield despite low yields. Except for the herb layer, little evidence was found of grazing influence on the vegetation structure and yield a few hundred metres away from livestock concentration points. On the other hand, the clearing of thickets for cropping led to severe soil erosion which threaten the resilience of 'brousse tigree'. These observations and the well-defined climatic, soil and topographic situations under which the 'brousse tigree' occurs invalidate the hypothesis of an anthropic origin of that vegetation pattern.